2002
DOI: 10.1128/jcm.40.6.2199-2206.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure ofCandida glabrataPopulations in AIDS and Non-AIDS Patients

Abstract: Analysis of the population genetics structure of natural populations elucidates the functioning and evolutionary capabilities of natural populations. It is particularly appropriate for organisms that cannot be directly observed (37). Indeed, the genotypic structure can provide useful clues for estimating the reproductive mode, gene flow, geographical structure, and approximate sizes of reproductive units (10).Infectious diseases involve organisms whose population biology is difficult to assess. This is why mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
4
21
2
Order By: Relevance
“…When these isolates were analyzed for their drug susceptibilities, no correlation between reduced susceptibility and the MLST or the PFGE genotype was found, which is in concordance with the findings presented in previous reports (15,16). No correlations were found between genotypes and clinical information, such as anatomic sources and hospital origin.…”
Section: Discussionsupporting
confidence: 90%
“…When these isolates were analyzed for their drug susceptibilities, no correlation between reduced susceptibility and the MLST or the PFGE genotype was found, which is in concordance with the findings presented in previous reports (15,16). No correlations were found between genotypes and clinical information, such as anatomic sources and hospital origin.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the most representative C. glabrata groups in Europe, the United States, and Japan were groups I and II, groups II and III, and groups III and IV, respectively. The population structure of C. glabrata is believed to be predominantly clonal (5). The results we have obtained on geographical specificity tend to support the conclusion that mixing between clades is depressed.…”
Section: Discussionsupporting
confidence: 75%
“…These have included the description of phenotypic switching (19,20), the demonstration of pseudohypha and tube formation (4,19), and the identification and characterization of a mating system that is similar to that of Saccharomyces cerevisiae (41,44). Studies of the population structure of the organism have also begun to emerge (5). To facilitate the latter, we have developed and begun to characterize a fingerprinting method based upon multilocus sequencing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, few tools are available to study the source of contamination, cross-contamination of patients at risk, and the biology of this yeast, which has, unlike C. albicans, a haploid genome (10). Studies of population structure have begun to emerge using enzymatic and randomly amplified polymorphic DNA typing (6) or sequencing of the cytochrome c oxidase subunit 2 gene (24). Recently, a technique based on the sequencing of six variable-locus genes, or multilocus sequence typing (MLST), has been proposed as a powerful typing method (7).…”
mentioning
confidence: 99%